Assyrian Entrepreneurship in Exile: Social Networks, Ethnic Capital, and Conflict Management in a Stateless Diaspora - Kerimo, Feyyaz (Archives of Business Research, 2025)
This paper examines the entrepreneurial practices of Assyrian migrants in Sweden, a stateless diaspora with a complex history of displacement and marginalization. Using the theoretical frameworks of mixed embeddedness and social capital, the study explores how Assyrian entrepreneurs navigate structural constraints, mobilize ethnic resources, and manage conflicts within family and community networks. Based on qualitative interviews and documentary analysis, the findings demonstrate three key contributions: (1) extending the mixed embeddedness framework to stateless diasporas, (2) theorizing ethnic capital under coercive and exclusionary conditions, and (3) identifying conflict management patterns that reflect both cultural continuity and adaptive innovation. The study offers theoretical and practical implications for understanding entrepreneurship in marginalized and politically constrained contexts, and contributes to broader debates on migrant entrepreneurship, diasporic agency, and the role of social networks in economic adaptation.